Trade and investment relations between the Community of Latin American and Caribbean States (CELAC) and its strategic extraregional partners (UN ECLAC SantiagoCL, 2015)
Gives an overview of figures in trade and investment relations between CELAC and the countries and groupings it has identified as strategic extraregional partners.
Keywords: INTERNATIONAL TRADE